2016
DOI: 10.18632/oncotarget.9702
|View full text |Cite
|
Sign up to set email alerts
|

The posteriorHOXDlocus: Its contribution to phenotype and malignancy of Ewing sarcoma

Abstract: Microarray analysis revealed genes of the posterior HOXD locus normally involved in bone formation to be over-expressed in primary Ewing sarcoma (ES). The expression of posterior HOXD genes was not influenced via ES pathognomonic EWS/ETS translocations. However, knock down of the dickkopf WNT signaling pathway inhibitor 2 (DKK2) resulted in a significant suppression of HOXD10, HOXD11 and HOXD13 while over-expression of DKK2 and stimulation with factors of the WNT signaling pathway such as WNT3a, WNT5a or WNT11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 48 publications
3
24
0
5
Order By: Relevance
“…Specifically, HOXB2, HOXB3, HOXB6, HOXB7, HOXB8, HOXB13, HOXD4, HOXD9 and HOXD11 were downregulated upon JIB-04 treatment in A673 cells (Figure 3B and 3C ), and the majority of these were also downregulated in TC32, SK-ES-1 and SK-N-MC cells (Figure 3C ). Notably, all but one of these (HOXD4) have previously been implicated in the promotion of cancer, and HOXD11 has specifically been demonstrated to be disease-promoting in Ewing Sarcoma [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, HOXB2, HOXB3, HOXB6, HOXB7, HOXB8, HOXB13, HOXD4, HOXD9 and HOXD11 were downregulated upon JIB-04 treatment in A673 cells (Figure 3B and 3C ), and the majority of these were also downregulated in TC32, SK-ES-1 and SK-N-MC cells (Figure 3C ). Notably, all but one of these (HOXD4) have previously been implicated in the promotion of cancer, and HOXD11 has specifically been demonstrated to be disease-promoting in Ewing Sarcoma [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…[35]). The current work sheds further light on the molecular mechanisms that contribute to posterior HOXD gene deregulation in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…The secreted, mature form of the glycoprotein is a key factor in chondrocyte proliferation and development and simultaneously inhibits terminal chondrocyte hypertrophy and endochondral ossification (Klinger et al ., ; Shukunami and Hiraki, ). These characteristics indicated that CHM1 might be important in ES malignancy, as ES progenitor cells seem to be of premature chondrogenic origin arrested at early osteo‐chondrogenic differentiation (Hauer et al ., ; von Heyking et al ., ; Tanaka et al ., ).…”
Section: Introductionmentioning
confidence: 97%